1996
DOI: 10.1021/jf950721v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soaking and Cooking on the Saponin Content and Composition of Chickpeas (Cicer arietinum) and Lentils (Lens culinaris)

Abstract: Changes in the saponin content and composition of both chickpeas (Cicer arietinum) and lentils (Lens culinaris) were investigated after the seeds were soaked in distilled water, citric acid, and sodium bicarbonate solutions. The effect of cooking for 30, 60, 90, and 120 min after the seeds were presoaked in distilled water was also studied. Soaking did not modify the saponin content or composition of chickpeas and lentils regardless of the pH of the soaking solution. The native saponin, soyasaponin VI, was par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
55
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 23 publications
4
55
0
1
Order By: Relevance
“…The processing regimens caused significant saponin loss of 34-53 % in P. roxburghii. Ruiz et al (1996) reported a detailed vision on saponin loss of chickpeas and lentils by various soaking medium (water, citric acid and NaHCO 3 ) and cooking times and found that neither the content nor the composition of saponins was affected by soaking regardless of the pH of the soaking solution. Saponin loss on natural (60-76 %) and controlled fermentation (100 %) of P. vulgaris varieties has been registered by Shimelis and Rakshit (2008).…”
Section: Saponinsmentioning
confidence: 99%
“…The processing regimens caused significant saponin loss of 34-53 % in P. roxburghii. Ruiz et al (1996) reported a detailed vision on saponin loss of chickpeas and lentils by various soaking medium (water, citric acid and NaHCO 3 ) and cooking times and found that neither the content nor the composition of saponins was affected by soaking regardless of the pH of the soaking solution. Saponin loss on natural (60-76 %) and controlled fermentation (100 %) of P. vulgaris varieties has been registered by Shimelis and Rakshit (2008).…”
Section: Saponinsmentioning
confidence: 99%
“…It has been reported that inclusion of legumes in the daily diet has many beneficial effects in the control and prevention of chronic metabolic diseases such as diabetes mellitus and coronary heart disease (Sagratini et al, 2009). Moreover, cooked legumes are considered an excellent source of vegetable proteins, and are also rich in starch, dietary fiber, minerals, and vitamins (Ruiz et al, 1996). While many research groups have focused their studies on specific bioactive components such as phenolics (Duenas, Sun, Hernandez, Estrella, & Spranger, 2003) or cholesterol lowering soyasaponins (Sagratini et al, 2013;Vila-Donat et al, 2014), there are few studies concerning the lipophilic phytochemical contents or the fatty acid (FA) profile of legumes (Konopka, Czaplicki, & Rotkiewicz, 2006;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These have been reported in lupins (Woldemichael et al, 2003), lentils (Morcos et al, 1976;Ruiz et al, 1996), chickpeas (El-Adawy, 2002), various beans and peas (Shi et al, 2004). Saponin content may vary even among the same species of edible beans, because of variations in cultivars (Khokhar and Chauhan, 1986), locations (Fenwick and Oakenfull, 1983;Price et al, 1987), irrigation condition, type of soil, climatic and environmental conditions.…”
Section: Saponinsmentioning
confidence: 87%